Knowledge, perception & contraception use and factors associated with contraception non-use among women with diabetes - Ngah, Nor Asyura (2017)
Introduction: Globally, the prevalence of diabetes is currently increasing in trend. In Malaysia, similar trend is reported by The National Health and Morbidity Survey (NHMS) 2015. The survey has reported that the prevalence of diabetes is high in young adults. Thus, more women from younger age group with diabetes in Malaysia will be facing a great reproductive risk. We are interested to evaluate the contraception use, the knowledge on contraception and the perception towards contraception practice among diabetes women with unmet need for contraception. Objectives: To study the knowledge, perception and practice of contraception and factors associated with contraception non-use among diabetic women in reproductive age attending outpatient clinic, in a tertiary hospital. Methodology: This is a cross sectional study involving 324 patients aged 18 years old to 50 years old with Type 1 or Type 2 Diabetes Mellitus. Simple random sampling with replacement method was applied to select participants who attended outpatient clinic and Diabetes Centre of a tertiary hospital from March 2015 to May 2015. Self-administered questionnaires were used to obtain the socio demographic characteristics and clinical data. Another part of questionnaires was used to assess practice of contraception, knowledge andperception towards contraception practice. The data were analysed for descriptive statistic and multiple logistic regression. Result: The median age of respondents was 45. Majority (72.2%) of diabetic women were contraception non-users. In all, 11.4% of diabetic women have good knowledge regarding contraception effectiveness and safety, prepregnancy care and pregnancy risk with regards to diabetes. A sizeable 54.6% of respondents showed satisfactory perception towards contraception practice. There was no significant association (p = 0.168) between knowledge and perception towards contraception. Factor significantly associated with contraception non-use were being Malay (OR=2.63, 95% CI 0.18, 0.83, p=0.015), being older-age (OR=6.32, 95% CI 4.23, 10.68, p=<0.01), and being diabetic women with successful pregnancy history (OR=0.12, 95% CI 0.06, 0.38, p<0.01). Conclusion: There is high prevalence of contraception non-use among diabetic women in reproductive age. Majority of respondents have poor knowledge on contraception. Despite having poor knowledge, majority of respondents have satisfactory perception towards contraception. Contraception non-use was more likely associated with being Malay ethnic and older-age. Meanwhile, being diabetic woman with previous successful pregnancy is protective from being contraception non-user.